(3fXe GddBdj HGdeGFI GdYhGdjs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s ((3eOQSI bGjJHGi s)
(3ChdgG (B:s
(3aEf GdMOjK GdfHhj GdeQahY fQJH JMJg Ydhe GdESdGe hEf ENJda efgG GdhVhA s
(3BNQgG (B:s
(3hef jLYd Gddg dg fhQkG adf jSJWjY CMO Cf jWaFg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MOjK JjehQ (B440) s
Keywords: (3GdMOjK h GdeUWdMs